Analisis Kualitas Pelayanan Kerja Pegawai Pada BKKBN Provinsi Sumatera Utara - Novianna Hasian Fernanda Simanjuntak; Yeni Ariesa (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
BKKBN stands for National Population and Family Planning Agency. The BKKBN is one of the non-ministerial government institutions under and responsible to the President through the Minister of Health. The benefit of this research is to add insight and knowledge, regarding the service system and employee development at the BKKBN of North Sumatra Province. This is marked by the existence of training and coaching that has been provided by Government Institutions which have also provided development, training, coaching, and directing facilities